2005
DOI: 10.1111/j.1744-7909.2005.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Dihydroflavonol 4-Reductase Genes Involved in Anthocyanin Biosynthesis in Purple Grains of Wheat

Abstract: Abstract:The grain color of wheat (Triticum aestivum L.) is an important characteristic in crop production. Dihydroflavonol 4-reductase genes (DFR) encode the key enzyme dihydroflavonol 4-reductase, which is involved in the pigmentation of plant tissues. To investigate the molecular mechanism of anthocyanin deposition in grains of wheat, we determined the expression of the wheat DFR gene in purple grains of cultivar Heimai 76. The results showed that DFR transcripts were localized in the seed coat of purple gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…1b). RT-PCR analysis using DFR-specific primers designed based on previously reported sequences (Yang et al 2003;Himi and Noda 2004;Liu et al 2005) and RNA sequence analysis (Shin et al 2015) showed that TaDFR-Is were highly expressed in the Iksan370 lines but not in Keumkang seedlings (Fig. 1c).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…1b). RT-PCR analysis using DFR-specific primers designed based on previously reported sequences (Yang et al 2003;Himi and Noda 2004;Liu et al 2005) and RNA sequence analysis (Shin et al 2015) showed that TaDFR-Is were highly expressed in the Iksan370 lines but not in Keumkang seedlings (Fig. 1c).…”
Section: Resultsmentioning
confidence: 75%
“…Wheat genomes contain three homologous DFR genes (TaDFR-A on chromosome 3A, TaDFR-B on chromosome 3 B, and TaDFR-D on chromosome 3D). These genes are highly expressed in red (Yang et al 2003;Himi and Noda 2004) and purple (Liu et al 2005) wheat grains. Furthermore, transgenic Arabidopsis plants that strongly express TaDFR-A (from purple-grained wheat) in their seed coats and pericarp tissue contain high levels of anthocyanin, demonstrating that TaDFR-A has the same function as Arabidopsis DFR (Liu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the up-regulated genes, dihydroflavonol 4-reductase catalyzes the metabolism of flavonoids, which are strong antioxidants and can increase the disease resistance of the plant (Liu et al 2005;Xu et al 2006). 1,4-Dihydroxy-2-naphthoate prenyltransferase is involved in the synthesis of vitamin E, which is a direct remover of O 2 -; together with superoxide dismutase and glutathione peroxide, it forms a plant's antioxidant system to protect the cell membrane and the nuclear acids in the cell from free-radical attack (Ge and Zhong 2007).…”
Section: Genes Related To Resistant Responsementioning
confidence: 97%
“…In different species, based on the different substrates selectivity of DFR, which gave rise to the anthocyanins with different colors, and then gave distinct colors to all kinds of species (Liu et al, 2005). For example, DFR is able to restore three kinds of substrate efficiently in gerbera (Johnson et al, 2001), however, in petunidin and orchid, DFR can efficiently restore DHQ and DHM, while DHK can't be restored.…”
Section: Introductionmentioning
confidence: 99%